PEMANFAATAN APLIKASI SRIKANDI BAGI PEGAWAI DI PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA REGIONAL BUKITTINGGI - Adra, Ayang; Permana, Iip (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2023)
The Srikandi application is a general government application that is useful for supporting the management and administration of documents electronically and saves paper use. This study aims to determine the use of the Srikandi Application for employees at the Bukittinggi Regional Human Resource Development Center. The main problems regarding the utilization and use of the Srikandi application for employees include limited access and infrastructure, no notifications from the Srikandi application, lack of socialization, training and understanding and lack of standardization in the use of the Srikandi application. This type of research is a qualitative research with descriptive method. Which describes the level of utilization and use of the Srikandi application based on the variables Performance Expectancy, Effort Expectancy, Facilitating Conditions, Standardization, solution and provides recommendations. The model used in this study is the modified Unified Theory of Acceptance and Use of Technology. The informants in this study used a purposive sampling technique. This data the writer obtained by conducting interviews, observations, and documentation using interview guidelines and recordings. The data analysis technique used is the MAXQDA application. The results of this study indicate that the majority of employees' interest in adopting the Srikandi application based on the six variables has quite good results, because this application has benefits for employees and agencies to make administrative and filing work easier, more accountable, and easier to use and learn